Economic Dispatch of Microgrid in Southwest China Based on Two-Stage Robust Optimization - Mingkui WEI; Quan ZHOU; Hong ZHOU; Shaorong CAI; Li JIANG; Liang LU; Wenju LIANG; Li SHEN; Qi LI (Zhongguo dianli)
According to the characteristics of abundant renewable energy reserves in southwest China, considering the influence of the uncertainty of renewable energy output and load on the operation scheduling of micro grid, this paper establishes a two-stage robust optimization economic dispatching model to obtain the economic optimal solution of the system under extreme operating scenarios. The model considers system power balance, output power constraints, demand response load constraints, and interaction constraints between microgrid and distribution network. The uncertainty in microgrid is dealt with through uncertain adjustment parameters, and the conservatism of the model is adjusted. Then Benders decomposition algorithm is used to solve the main problem and sub-problem of the model, and duality theory is used to decouple the inner layer model. Finally, the results verify the effectiveness of the proposed model, and provide a reference for the scheduling strategy after the microgrid is connected to the southwest power grid.